Morbidity and mortality in tuberculosis associated immune reconstitution inflammatory syndrome in children living with HIV: A narrative review - Haslina Hashim (Journal of Clinical Tuberculosis and Other Mycobacterial Diseases, 2023)
Tuberculosis-associated immune reconstitution syndrome (TB-IRIS) is an increasingly recognized complication of children living with HIV who are receiving treatment for active tuberculosis (TB). The purpose of the study was to appraise available evidence of morbidity and mortality related to TB IRIS among the paediatric population. A non-systematic review of the literature was conducted by retrieving records from Scopus, PubMed and Google Scholar). Four specific research questions assessing the risk factors (age, undernutrition, extrapulmonary TB and degree of immunosuppression) for TB-IRIS were discussed. The search yielded 370 articles, subsequently screened for eligibility according to the inclusion criteria. The majority of the articles were adult studies. Six studies were identified: Three retrospective and three prospective studies. The majority of the studies were conducted in TB/HIV-endemic countries. Only one study addressed mortality due to TB-IRIS as an outcome. A total of 6 mortalities related to TB-IRIS were reported. Advanced immunosuppression is universally agreed as an established risk factor for mortality in TB-IRIS in children. The severe presentation was more common in children with extrapulmonary tuberculosis. There is a paucity of data available on mortality in HIV-infected children with TB-IRIS. Future research is needed to assess the predictive factors of morbidity and mortality in HIV-infected children with TB-IRIS especially in low resource and high endemic countries.